(untitled) - Cronin, Bruce (Cambridge, UK,New York, 2003)
Bruce Cronin develops a theory that links international stability with progress in building a cohesive international order. He examines how states attempt to provide for international stability by creating International Protection Regimes--multilateral institutions designed to protect clearly defined classes of people within sovereign states. Cronin argues that, in the aftermath of major systemic changes, states try to create international orders by regulating the relationship between governments and their populations, particularly in newly formed and reorganized states.
Keywords: Minorities,Civil rights,International relations,Dân tộc thiểu số,Quyền công dân,Quan hệ quốc tế; Civil rights,Quyền công dân